Important Factors for User-Generated Content for Tourists Visiting Ciwidey Nature Tourism - Alimansyah, Muhammad Yusuf Iskandar; Octaviany, Vany (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Social media has become the main means in this digital era to share experiences and obtain information on tourist attractions in the form of user generated content which is used as material for tourists to consider when visiting tourist attractions in an area, one of which is the Ciwidey tourist area. This research aims to identify important factors from user generated content on social media for tourists visiting Ciwidey Nature Tourism. This research was carried out with a quantitative descriptive research approach using nonprobability sampling in the form of purposive sampling and factor analysis methods as well as data collection techniques by distributing online questionnaires to tourists who have visited the Ciwidey tourist area. The results of this research show that there are four important user generated content factors including content quality, content attractiveness, level of contribution, and content reputation and popularity with content quality being the most important factor in its contribution to tourists' decisions to visit Ciwidey natural attractions.